2020
DOI: 10.3390/jfmk5020028
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Training with Weightlifting Catching or Pulling Derivatives on Squat Jump and Countermovement Jump Force–Time Adaptations

Abstract: The purpose of this study was to examine the changes in squat jump (SJ) and countermovement jump (CMJ) force–time curve characteristics following 10 weeks of training with either load-matched weightlifting catching (CATCH) or pulling derivatives (PULL) or pulling derivatives that included force- and velocity-specific loading (OL). Twenty-five resistance-trained men were randomly assigned to the CATCH, PULL, or OL groups. Participants completed a 10 week, group-specific training program. SJ and CMJ height, prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Relative MF, F PP , and PP were calculated by dividing each magnitude by the participant’s BM. Finally, time-normalized force–time curves of each exercise performed at each load were produced using previously outlined procedures [ 23 ]. Using this method, we resampled force–time data to 500 data points in which each data point corresponded to 0.2% of the total movement time.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative MF, F PP , and PP were calculated by dividing each magnitude by the participant’s BM. Finally, time-normalized force–time curves of each exercise performed at each load were produced using previously outlined procedures [ 23 ]. Using this method, we resampled force–time data to 500 data points in which each data point corresponded to 0.2% of the total movement time.…”
Section: Methodsmentioning
confidence: 99%
“…Additional researchers examining the HEXJ concluded that PP occurred with loads ranging from 20–40% of a 1RM back squat [ 5 ] or 10–20% of a 1RM box squat [ 12 ]. Compared to the other two exercises, the JShrug is typically loaded using a percentage of a 1RM weightlifting catching derivative [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. In this light, PP has been shown to be maximized between 30–45% of a 1RM hang power clean [ 14 , 16 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Modified reactive strength index was then calculated as the ratio between jump height and time to takeoff (Suchomel et al, 2015). Time-normalized forcetime and displacement-time curves were generated using previously described methods (Suchomel et al, 2020). PF during the IMTP was identified as the greatest force produced following the initiation of the IMTP (visually identified as the first increase in force following the pre-tension phase of the movement) (Beckham et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Researchers have concluded that weightlifting movements and their derivatives may provide greater strength, power, and speed adaptations compared to other methods of training [ 1 ], especially when added to traditional resistance training programs [ 2 ]. A growing body of research has shown that training with weightlifting pulling derivatives (i.e., clean or snatch variations that exclude the catch phase) [ 3 ] may improve dynamic and isometric strength, jump performance, sprint speed, and change of direction performance [ 4 , 5 , 6 , 7 ]. This is due to the performance of these movements providing effective force and velocity overload stimuli via triple extension of the hip, knee, and ankle (plantarflexion) joints [ 3 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%